Molecular and radiocarbon constraints on sources and degradation of terrestrial organic carbon along the Kolyma paleoriver transect, East Siberian Sea - Vonk, J. E.; Sánchez-García, L.; Semiletov, I.; Dudarev, O.; Eglinton, T.I.; Andersson, A.; Gustafsson, O. (Biogeosciences, 2010)
Climate warming in northeastern Siberia may induce thaw-mobilization of the organic carbon (OC) now held in permafrost. This study investigated the composition of terrestrial OC exported to Arctic coastal waters to both obtain a natural integration of terrestrial permafrost OC release and to further understand the fate of released carbon in the extensive Siberian Shelf Seas. Application of a variety of elemental, molecular and isotopic (δ 13 C and Δ 14 C) analyses of both surface water suspended particulate matter and underlying surface sediments along a 500 km transect from Kolyma River mouth to the mid-shelf of the East Siberian Sea yielded information on the sources, degradation status and transport processes of thaw-mobilized soil OC. A three end-member dual-carbon-isotopic mixing model was applied to deduce the relative contributions from riverine, coastal erosion and marine sources. The mixing model was solved numerically using Monte Carlo simulations to obtain a fair representation of the uncertainties of both end-member composition and the end results. Riverine OC contributions to sediment OC decrease with increasing distance offshore (35±15 to 13±9%), whereas coastal erosion OC exhibits a constantly high contribution (51±11 to 60±12%) and marine OC increases offshore (9±7 to 36±10%). We attribute the remarkably strong imprint of OC from coastal erosion, extending up to ∼500 km from the coast, to efficient offshoreward transport in these shallow waters presumably through both the benthic boundary layer and ice-rafting. There are also indications of simultaneous selective preservation of erosion OC compared to riverine OC. Molecular degradation proxies and radiocarbon contents indicated a degraded but young (Δ14C ca. -60% or ca. 500 14 C years) terrestrial OC pool in surface water particulate matter, underlain by a less degraded but old (Δ14C ca. -500% or ca. 5500 14 C years) terrestrial OC pool in bottom sediments. We suggest that the terrestrial OC fraction in surface water particulate matter is mainly ...